Keragaman Produk, Lokasi dan Niat Kunjungan Ulang ke Pengecer - Rahayu Mardikaningsih; Ella Anastasya Sinambela (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2021)
The retail industry which continues to grow with the level of competition between actors creates a challenge for retailers to offer visitor appeal and meet the expectations of their visitors. Competition is not only between store owners in real terms but also retailers must face competition from online-based retailers. Modern retail shops must have an edge over their competitors in order to get continuous visits from the public. This study aims to analyze and determine the effect of product diversity and location variables on the intention of returning to retailers. By involving 100 respondents, it was found that the results of the study stated that the two independent variables had a significant influence on the dependent variable.